(untitled) (Revista Científica Compendium, 2017)
The present article has as purpose to present the proposal of a theoretical model of dynamic capacities, from the analysis of the internal facilitators of the absorption process. In this sense, four scenarios of the organization’s location are deployed according to their ability to absorb knowledge, making it possible to adequately identify their competencies, improve their performance and efficiently take advantage of the opportunities that arise, allowing characterizing a particular organization in a determined time. The contribution of this model that establishes different levels when describing the dynamic capacity is determined by the utility it can provide in the understanding and management of the administrative and managerial processes. Although it is necessary to contrast it empirically in order to reaffirm the theoretical sustenance or make any adjustments that may result.